JURIDICAL ANALYSIS OF CORPORATE CRIMINAL LIABILITY ON INDUSTRIAL AFFAIR DISPUTES, A COMPARATIVE LAW STUDY BETWEEN INDONESIA AND NEW ZEALAND - Hamzah Nurhasan (Jurnal Hukum Khaira Ummah, 2021)
This research was conducted on the application of corporate criminal liability legislation in Indonesia which is compared with the application of corporate criminal liability legislation in New Zealand, with a long-term goal is to harmonize the regulation of corporate criminal liability, so there will be the realization of legal certainty, public benefit, and justice in the law enforcement in Indonesia. The realization of legal certainty, public benefit, and justice is still so much to be realized considering the various diversity of the formulation of corporate criminal liability under applicable legislation in Indonesia. To support harmonization in the regulation of corporate criminal liability in the legislation, there must be a review of the regulation of corporate criminal liability in New Zealand as a comparison, how the arrangement of corporate criminal liability in New Zealand which is based on the common law system? How is the concept of corporate criminal liability arrangements in accordance with the standards of international law?Keywords: Corporation; Criminal Liability; Comparative Law Studies.